Clinical and microbiological study of antimicrobial activity of ozone in the treatment of chronic periodontitis in children (Эндодонтия Today, 2020)
The aim of the study was to estimate the efficiency of the local ozone and contact darsonvalization or root canal system of permanent teeth with chronic periodontitis based on clinical and microbiological studies. We observed eight patients aged 6 to 13 years with chronic apical periodontitis (ICD-10). Microbiological research includes conducting bacteriological seeding biomaterial (16 root canals), isolated from the contents of the root canals of permanent teeth with incomplete root formation in children with chronic apical periodontitis. The study found ozone therapy is effective against microorganisms containing the root canal of the permanent teeth in children, which would substantially reduce the number of possible odontogenic inflammatory diseases of maxillo-facial area.